ANALISIS YURIDIS PUTUSAN NOMOR: 115/PDT.SUS- MEREK/2022/PN.NIAGA. JKT.PST TENTANG SENGKETA MEREK DAGANG KASO DAN KASOMAX - Ruhtiani, Maya; Abrillia, Marcella; Hafny Afrilies, Marlia (LPPM Universitas Harapan Bangsa, 2025)
This study examines the trademark dispute between PT Tatalogam Lestari (owner of the